Management of an integrated network of wastewater treatment plants for improving water quality in a river basin. Issue 1 (2019) - Robles-Rodriguez, C.E.; Ben-Ayed, A.; Bernier, J.; Rocher, V.; Dochain, D.
Abstract: Preserving water quality along a river basin is a multi-factorial task that depends on the management of sewers, wastewater treatment plants (WWTPs), and the dynamics of the river. This paper presents a control strategy of a reduced integrated network of WWTPs that can be used as a reference point for designing, evaluating and performing more complex strategies. The reduced network considers that the outflow of the sewers is gathered in one point from which it is distributed to three WWTPs that can treat and/or by-pass the wastewater into the river. The control strategy makes use of Model Predictive Control (MPC) and global optimization tools, such as Particle Swarm Optimization (PSO). The single input is first divided into three via PSO (one inflow per treatment plant) with a further partition into six discharging parts (two per treatment plant). Two scenarios in rain period were evaluated to improve the quality of the river regarding the concentrations of ammonium and nitrites. Simulation results showed that the control strategy improved the mean and the transient conditions of both concentrations. Further studies about the stability of the interconnected system should be evaluated.